Factors determining Performance appraisal practices in Pharmaceutical Companies in Punjab: An Empirical Study (Journal of Pharmaceutical Negative Results, 2023)
Performance Appraisal is the process where an organization assesses how theemployees are performing in the company is called. The system of appraisal judges what an employee is doing for the company and what a company should give them in return as an appreciation for their good work and the dedication they have shown towards their job and company. The process can also be called a process that analyzes the capabilities of an employee to perform, and it also finds out the deficiencies or shortcomings that the capabilities can be appreciated and deficiencies can be overcome with the help of training and developments. This study follows a quantitative approach for analysis Primary data have been collected from employees of pharmaceutical companies through a structured questionnaire. The sample size of the study is 390 respondents. The respondents were selected through judgmental sampling. For analysis of data, exploratory factor analysis was applied.The factors determining performance appraisal system are Planning and Goals, Feedback System, Employee benefits (non-tangible), Employee Benefits (Tangible), and setting the standards